Surgical tactics of treatment in patients, suffering an acute arterial ischemia of the lower extremities on background of atherosclerotic arterial affection - M. M. Akhmad; F. M. Akhmad (Клінічна хірургія)
Objective. To improve the diagnosis and to optimize a surgical tactics of treatment in patients, suffering an acute ischemia of the lower extremities, severe stage of the extremity ischemia, depending on the prognostic criteria for surgical treatment revealed. Materials and methods. There were examined 70 patients, suffering an acute arterial occlusion: men - 44 (63%), women - 26 (37%) ageing (65.2 ± 3.5) yrs old. The patients were distributed into three groups: the 1st - 32 (45.7%) patients with the arteries embolism revealed, the second - 5 (7.1%) patients with the lower extremities idiopathic arterial thrombosis, and the third - 33 (47.1%) patients with arterial thrombosis, which have developed on background of their atherosclerotic affection. In all the patients there were conducted a general clinical examination, ultrasonographic duplex scanning of the lower extremities arteries, spiral CT with contrasting. In 54 patients a degree of the skeletal muscles damage and a state of the acid-base balance were studied up.